Understanding Katishool And Its Management In Ayurveda W.S.R. To Kati Vasti: A Review - Joshi, Shruti; Mewal, Jyoti; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2020)
Katishool has become a common disorder involving the muscles and bones of the back. The disorders which affect the locomotive system have increased in today time. These conditions significantly scale back the human activities in terms of social as well as professional life. Shool in Kati Pradesh is Pratyatmaka lakshan of Katishool. The Shool is of varied varieties, which happen by Prakupita Vata Dosha. In a typical case of Katishool, pain is confined to Kati Pradesh or Lumbo-sacral and Sacro-iliac region solely. Numerous treatment choices as mentioned in modern medicine like analgesics, anti-inflammatory drugs, physiotherapy, spinal exercises etc. have their own limitations. The classical treatments in Low Back Ache like Panchkarma (five purification procedures in Ayurveda) procedure therapies preceded by Snehana and Swedana used for relaxation further as giving tone to the muscles and for promoting the blood circulation are substantially useful which pacify the Prakupit Vata Dosha, increase strength of the person, maintains health and longevity. Mridu Virechan and numerous Vasti Karma destiny as useful in eradicating the Prakupit Vata Dosha. Kati Vasti, a procedure within which both the properties of Snehana and Swedana are incorporated is an efficient remedy. An effort has been made to understand Katishool and its treatment procedures in Ayurveda and understanding Kati Vasti in detail.